DAMPAK PEMAKAIAN DAN PERAWATAN LENSA KONTAK LUNAK DI OPTIK MANDIRI PADANG - D.I Suryanta (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
This article discusses the impact of using and maintaining soft contact lenses at Optik Mandiri Padang, the use of contact lenses has many negative impacts that users need to be aware of, especially if they do not follow the usage rules. This type of research is descriptive quantitative. The population in this study were all patients wearing soft contact lenses during the study. Sampling in this study is a total sampling technique. The data were collected through a questionnaire, then the data were discussed in accordance with the theory proposed in the literature review. The results showed that respondents did not understand the impact of improper use and care of soft contact lenses, this can be seen as many as 14 respondents (46.7%) knew about the correct use and care of soft contact lenses (soft lenses) for eye health and 16 respondents (53.3%) do not know about the correct way to use and care for soft contact lenses for eye health, 13 respondents (43.3%) know about the impact of wearing and caring for soft contact lenses (soft lenses) that are incompatible with standard and as many as 17 respondents (56.7%) do not know about the impact of wearing and caring for soft contact lenses (soft lenses) that are not in accordance with standards, 11 respondents (36.7%) know about the handling of the use and care of soft contact lenses ( contact lenses) and as many as 19 respondents (63.3%) did not know about the handling of the use and care of soft contact lenses (soft lenses. Based on the results of this study, there are several Several suggestions were conveyed, namely for the public when wearing and caring for contact lenses must pay more attention to proper use and care so as not to have an impact on eye health, RO provides information to patients about how to use and care for soft contact lenses (soft lenses) that are correct for health eyes and provide information about the impact of wearing and caring for soft contact lenses (soft lenses) that are not in accordance with standards.